Presence of antibiotic resistant bacteria along the pharmaceuticals production line - Makky, Essam A.; Ibrahim, Mohamed M.; El-Gamal, Mamdoh S. (Elsevier Ltd, 2013)
The antimicrobial susceptibility of forty-five bacterial isolates obtained from different pharmaceutical raw materials of several companies in Cairo, Egypt during June to august, 2008 was determined using agar diffusion method. Only fourteen out of forty-five antibiotic resistant bacterial isolates were selected according to their sensitivity to equal or more than two antibiotics used. Isolates were subjected to antimicrobial susceptibility testing. The percent of resistance to seven antibiotics were Colis. (16.7%), Azithr. (78.6%), Oxytet. (0.0%), Amox. (21.4%), Kan. (42.8%), Cipro. (0.0%), and Spictin. (100.0%). Active potency of the raw materials was determined by incubating the drugs with and without microbes using HPLC and UV spectrophotometer. Among 14 selected isolates two were found to contain plasmids that are probably related to their drug resistance.